Legal Protection for Justice Collaborators in Indonesia’s Criminal Judiciary System - Hidayatullah Hidayatullah (Universitas Airlangga, 2019)
One way to assist law enforces to prevent and combat crime is to involve justice collaborators. Justice collaborators are crucial in assisting law enforcers to expose perpetrators of organized crime as well as transnational crimes. The lack of a legal regime that provides rights to a justice collaborator will impact the interest of a person to become a justice collaborator. Legal protection for justice collaborators must also include protection to his/her family both physically and psychologically. One method of appreciation that can be given to justice collaborators is through the special treatment of criminal offences. One form of special treatment in regards to criminal cases involving justice collaborators within the criminal judiciary may utilize the plea bargaining approach as a method of legal protection towards justice collaborators. To make more efficient the process of determining criminal sanctions to justice collaborators will contribute to the legal certainties owed to justice collaborates as a rightful reward of their contribution in extraordinary crimes. The criminal judicial system that utilized the plea bargaining approach for justice collaborators has the advantage of the absence of criminal examinations.